Issues for Enforcement of Decisions of the International Investment Arbitration on Temporary Protection Measures (Texas Journal of Multidisciplinary Studies, 2022)
In recent years, many of the leading arbitral institutions have amended their rules in order to make arbitration more responsive to users' needs. A key development has been the introduction of emergency arbitrator procedures, which enable parties to obtain urgent relief before the substantive tribunal is formed. For good reason, these new mechanisms are receiving significant attention from parties and arbitrators. However, have enforcement mechanisms kept pace with these developments? Therefore, this article addresses the implementation of interim measures of relief issued by international arbitral tribunals through exploring current legal frameworks for such enforcement, foreign case law practices, examples of such measures that have been enforced and suggestions for drafting interim measures as well as alternatives for harmonizing into international framework to maximize their potential enforceability